Adolescents’ experiences of psychological treatment for gaming disorder: a qualitative study - Bore, Per; Leo, Jenny; Garpenhag, Lars; Claesdotter-Knutsson, Emma (Frontiers in Psychiatry, 2025)
BackgroundGaming disorder is a recently recognized psychiatric condition and a growing public health concern, particularly among adolescents. Despite this, there is limited research on what kind of treatment they need. Existing studies are mostly quantitative and offer limited insight into adolescents’ lived experiences.AimThe aim of this qualitative study is to explore how adolescent patients perceive their gaming as a problem and their experiences of psychological treatment for gaming disorder.MethodWe used a qualitative descriptive approach and conducted semi-structed interviews with eight male patients (aged 13–19) about their experiences of psychological treatment for gaming disorder at a specialized clinic. The treatment is a combination of cognitive-behavioral therapy (CBT) and family therapy. The interviews were analyzed using thematic analysis.ResultsParticipants generally reported positive treatment experiences, especially the value of combining family therapy with individual CBT. They appreciated the broad focus of the treatment, which addressed not only gaming but also problems in other life areas such as school, sleep, and family relationships. Notably, most did not describe gaming as their main problem, but they connected their gaming to difficulties in other areas of life.ConclusionThese findings suggest that effective treatment for gaming disorder should address the broader psychosocial context in which gaming occurs. Patients do not always view gaming as their primary problem, and clinicians should be cautious about framing it as such. Instead, gaming should be explored in connection with other life difficulties. It is helpful when clinicians demonstrate knowledge about gaming and avoid coming across as critical of the gaming. Integrating family therapy into CBT-based interventions appears clinically valuable and warrants further exploration.